EFEKTIVITAS BIOETANOL DARI LIMBAH BIJI MANGGA SEBAGAI HAND SANITIZER TERHADAP BAKTERI Staphylococcus aureus - Gunawan, Leo Van; Ghozali, Muhamad; Supriatun, Evi; Simanjuntak, Naomi Margaretha; Zainuddin, Zainuddin (Jurnal Buana Farma, 2024)
Indramayu is a mango producing area in West Java Province. There are many varieties of mango types cultivated in Indramayu, including gedong gincu, gajah, harum manis, cengkir, golek, lali jiwa, agrimania and manalagi. In Indramayu, mangoes are sold as fruit and dodol. Mango seeds are simply thrown away or used as seeds. Mango seeds contain 81.3% starch per 100 grams. The starch in mango seeds can be made into flour as a raw material for making bioethanol. Bioethanol with a content of 70% can be used as an antiseptic to kill bacteria, viruses and fungi so that it can be used as a basic ingredient for making hand sanitizer. The method for making hand sanitizer from mango seed bioethanol goes through the Liquification Process, Saccharification Process, Fermentation Process, Distillation Process, Testing Bioethanol Content, Making Hand Sanitizer and Testing the Effectiveness of Hand Sanitizer on Staphylococcus aureus Bacteria using the disk diffusion method. The results of testing the bioethanol content after the multistage distillation process is 74%. Then bioethanol is mixed with Glycerin 99,7%, H2O2 3% and Sterile Aquadest to make hand sanitizer. The results of testing the effectiveness of hand sanitizers on Staphylococcus aureus bacteria showed that the diameter of the inhibition zone was 6 mm. Based on the Davis and Stout criteria, the effectiveness of hand sanitizer from mango seed waste bioethanol in inhibiting the growth of Staphylococcus aureus bacteria is medium.